2012
DOI: 10.1002/bse.1746
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Requirements, Knowledge Sharing and Green Innovation: Empirical Evidence from the Electronics Industry in China

Abstract: Building on the Porter hypothesis, which posits that regulatory stringency triggers innovation and thereby allows firms to achieve the dual purpose of environment protection and enhanced business performance, the present research develops an integrative model that explores the determinants of green innovation with a focus being placed on knowledge sharing. Data were collected from 203 green innovation project leaders from electronics manufacturers operating in China. The results indicate that knowledge sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(188 citation statements)
references
References 100 publications
5
142
0
12
Order By: Relevance
“…Some studies discussed the relationship between this norm and corporate performance [22,23]. The affiliated firms can strengthen their own financial performance by reducing transaction costs and by sharing both resources and risks with one another [24,25]. The benefits stemming from business-group structures as complementary assets can also increase the outcome of firms' environmental innovation [13].…”
Section: How Do Complementary Assets Support Smes To Improve Their Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies discussed the relationship between this norm and corporate performance [22,23]. The affiliated firms can strengthen their own financial performance by reducing transaction costs and by sharing both resources and risks with one another [24,25]. The benefits stemming from business-group structures as complementary assets can also increase the outcome of firms' environmental innovation [13].…”
Section: How Do Complementary Assets Support Smes To Improve Their Enmentioning
confidence: 99%
“…Firms also require intangible resource sharing for environmental innovation. For example, knowledge sharing assists firms to achieve an improvement in the performance of green product and process innovations [25]. As external benefits of the business-group affiliation, firms providing green products and services are likely to share the brand power of the business group because the firms cannot easily promote their environmental activities to customers and investors [11,37,58].…”
Section: Business-group Affiliationmentioning
confidence: 99%
“…Eco-innovation changes people's values and the sustainability of their lifestyle through green innovation processes [2]. Moreover, knowledge sharing is found to have a direct and positive association with green innovation processes and a positive impact on the development of eco-innovation by firms [38]. In addition, green innovation processes are alternatives to production and consumption that involve knowledge sharing among partners or employees, green innovation process research and development, and cooperation with suppliers [39].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…For instance, (a) The study by Yusuf et al (2014) reported innovation speed as the facilitating factor in the relationship between demand and eco-product innovation implementation [33], (b) S. K. S. Wong (2013) underscored the mediating role played by knowledge sharing in the green requirements and new green product success, and also for the relationship between green requirements and green product and process innovations [34], (c) Test results by Huo & Shan (2013) also showed that 70% of photovoltaic (PV) market in the twenty countries has insignificant market pull factor. They suggested that in order to encourage demand pull policy making is suggested to lead the market until it achieved stable growth [35], and (d) Kammerer (2009) emphasized empirical evidence that, with demand, customer benefits foster the implementation of eco-product innovations, their broad application and their level of novelty [14].…”
Section: Proposed Modelmentioning
confidence: 99%